Gambaran Kesehatan Mental Guru Sekolah Dasar (SD) Inklusi di Pekanbaru - Cut Aathirah Nurrady; Siregar, Juliarni (UIR Press, 2021)
The mental health of an inclusive teacher must be considered, because the demands of an inclusive SD teacher have more challenges such as lack of facilities to teach child with dissability, lack of knowledge about child with dissability that affects the mental condition of an inclusive SD teacher. This study aims to determine how the mental health picture of elementary school (SD) inclusion teachers in Pekanbaru. Subjects in this study were 182 teachers selected using cluster sampling. This study uses the Mental Health Inventory scale (MHI-38) compiled by Viet and Ware (1983) and adapted by Faizah and Amnah (2007). The analysis used is descriptive statistical analysis. The results of this study indicate the mental health of inclusive elementary school teachers in Pekanbaru is mostly in the medium category of 42.3%, meaning that most of the inclusive elementary school teachers have mental health that is neither high nor low either. The majority of psychological well-being and psychological distress are in the moderate category. When viewed from the age, length of teaching, and the work status of teachers it was found that there were no significant mental health differences, where the mental health of teachers tended to be moderate.